SAM: Preliminary Hybrid Model to Support Agile Large-Scale Transformation in Software Industries - Gómez-Campo, Cristian Esthibel; Cañizares-Hernández, Tania Guadalupe; Pardo-Calvache, César Jesús (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Agile scaled approaches have become an alternative to synchronize activities and interactions between large development teams. However, these do not describe the fundamental aspects to transform/evaluate the current approach of an organization. This paper presents the harmonization strategy used to obtain a preliminary hybrid model, called SAM, to support the agile transformation on a large scale in software industries. This model has been obtained from the homogenization, comparison and integration of the common practices of scaled models like SAFe, LeSS, Nexus and DAD. The hybrid model obtained describes the fundamental attributes to take into account to start the transformation or evaluate a scaled approach. In order to do this, it establishes and describes 18 documented practices that indicate what to take into account to scale/evaluate a large-scale approach used by a software company. With the obtained results, it can be seen that SAFe, LeSS, Nexus and DAD have aspects in common, and that it has been possible to unify them in SAM; therefore, the harmonization strategy presented and the proposed model could be very useful for professionals, consultants and companies trying to transform/evaluate their approaches.